Egyptian Intra Agriculture Trade with COMESA Trading Partners: A Gravity Model - Mahmood, Haider; Alkhateeb, Tarek Tawfik Yousef; Maalel, Nabil (International Journal of Economics and Financial Issues, 2017)
The regional trade provides better environment for any country to achieve the trade objective instead of a total free trade in this modern age. This study investigates the determinants of Egyptian agriculture trade with her 20 COMESA trading partners by using data of 1990-2015 and by applying Pooled Mean Group Estimators (PMG) on gravity model. Our results are confirming the panel cointegration in our model. Egyptian GDP and population are negatively influencing to the agriculture balance of trade. COMESA trading partners’ GDP and population have positive impact on the balance of trade. The exchange rate depreciation has unfavorable impact on agriculture balance of trade in the short run and has a favorable impact in long run. This is an evidence for presence of J-curve hypothesis in Egyptian trade in COMESA region and also showing an elastic behavior of exchange rate on balance of trade in the long run. Hence, this study recommends to Egyptian policy makers to adopt depreciation policy to correct agriculture balance of trade with COMESA trading partners. Keywords: Agriculture Balance of Trade, COMESA, GDP, Panel Cointegration JEL Classifications: E01, C33, F14, F53